2021
DOI: 10.1088/1361-6528/abd50a
|View full text |Cite
|
Sign up to set email alerts
|

SnO2 nanofibers prepared by wet spinning using an ordered porous alumina spinneret

Abstract: SnO2 nanofibers with uniform diameters were obtained by wet spinning using ordered anodic porous alumina as a spinneret, followed by heat treatment. Ordered alumina through-hole membrane is a suitable spinneret material for nanofiber spinning owing to its nanohole array structure with uniform-sizes holes. A polymer solution containing a Sn salt was used as a precursor solution for the wet spinning. Polymer nanofibers containing the Sn salt were continuously formed as the precursor passed through the alumina ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…SEM images of ordered anodic porous alumina before (a) and after 20 (b), 30 (c), and 40 (d) ALD cycles of Al 2 O 3 . The residual Al substrate was dissolved selectively in saturated iodine methanol solution at 50 °C for 1 h …”
Section: Resultsmentioning
confidence: 99%
“…SEM images of ordered anodic porous alumina before (a) and after 20 (b), 30 (c), and 40 (d) ALD cycles of Al 2 O 3 . The residual Al substrate was dissolved selectively in saturated iodine methanol solution at 50 °C for 1 h …”
Section: Resultsmentioning
confidence: 99%
“…Polymer nanofibers are generally made of two types of polymers, natural and synthetic [ 35 38 ], by melt-blown method [ 39 ], template synthesis [ 40 ], self-assembly method [ 41 ], direct stretching method [ 42 ], wet spinning method [ 43 ], electrostatic spinning method, centrifugal jet spinning method, plasma-induced synthesis, pressurized spinning, solution blowing spinning [ 44 ], and other methods. Most of these techniques, however, have certain drawbacks which limit their wide applications.…”
Section: Preparation Methods Of Polymer Nanofibersmentioning
confidence: 99%
“…14,15 We have reported that polymer nanofibers with uniform diameters could be obtained by extruding a polymer solution through holes of anodic porous alumina into a solidifying solution and that the diameter of the obtained polymer nanofibers can be controlled by changing the hole diameter of the anodic porous alumina spinneret. 16,17 In this process, for obtaining fine nanofibers, the aperture diameter has to be reduced. The problem to be solved, accompanied by the reduction in aperture diameters, is the pressure loss increase in the direction of depth in the spinneret.…”
Section: Introductionmentioning
confidence: 99%